Respuestas
Respuesta dada por:
0
en la de x+2y=-2 sale x+y=-1
Respuesta dada por:
0
-Despejando "x":
3x-5y=-28
x= (-28+5y)/3
-Reemplazando para hallar "y" :
(-28+5y)/3 + 2y = -2
5y - 28 = -6y -6
11y=22
y=2
- Reemplazando para hallar "x" :
x + 2(2) = -2
x=-6
y=2 ; x=-6
3x-5y=-28
x= (-28+5y)/3
-Reemplazando para hallar "y" :
(-28+5y)/3 + 2y = -2
5y - 28 = -6y -6
11y=22
y=2
- Reemplazando para hallar "x" :
x + 2(2) = -2
x=-6
y=2 ; x=-6
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años